Depolimerisasi Lateks Karet Alam Secara Kimia Menjadi Liquid Natural Rubber (LNR) Menggunakan Katalis Cocl2 Dengan Variasi Kadar Nano2 - Septian, Septian; Amraini, Said Zul; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Increase in derivative products from natural rubber latex with the depolymerization process to low molecular weight Liquid Natural Rubber (LNR). The use of CoCl2 and NaNO2 catalysts as degradation agents is believed to increase the efficiency of the depolymerization process. The purpose of this research is to synthesize LNR from natural rubber latex and determine the effect of NaNO2 levels and chemical depolymerization reaction time of natural rubber on the formation of molecular weight of Liquid Natural Rubber (LNR) products. The method used to produce LNR consists of several stages. The initial stage is the centrifugation of natural rubber latex which is the basic material in producing LNR. Then the main process is chemical depolymerization of natural rubber latex by the addition of degradation agents such as hydrogen peroxide, sodium nitrite and the cobalt diclloride (CoCl2) catalyst, which ends with the purification stage. The chemical depolymerization process uses a variation of the content of NaNO2 degrading agents which is 2, 3, 4 bsk (weight per hundred rubbers). The LNR results obtained will then be analyzed using FTIR and GPC analysis tools. The results of this study found that the content of NaNO2 is 4 bsk NaNO2 degradation levels of 126,448 g/mol. By using the chemical depolymerization process also undergoes the formation of functional groups such as carbonyl and hydroxyl groups. Keywords: depolymerization, dry rubber concentration, gel permeation chromatography, natural rubber latex, reaction time